(untitled) (Journal of Misan Researches, 2020)
Praise be to God, Lord of the worlds, and the best of prayers and blessings be upon our beloved, master, and physician of our souls Muhammad, and upon the pure and pure family of his household, and his chosen companions. Imam Al-Reza (peace be upon him) is the eighth imam of the people of the house (peace be upon him) the pure family whom the Prophet (may God’s prayers and peace be upon him and his family) commanded to adhere to with the Holy Qur’an after him because they have modified the Qur’an and its people who will not separate until they respond (peace be upon him and his family) And greeting) the basin. Imam Al-Ridha (peace be upon him) left us a huge legacy with what he (peace be upon him) reported from his companions and students of lessons, debates and discussions in all Islamic sciences in (the sciences of the Qur’an and its interpretation, the science of speech and belief, jurisprudence and its fundamentals, asceticism, morals, supplication, etc.), So Ibn Babawiya compiled his jurisprudence (peace be upon him) in a book he called (The Jurisprudence of Ridha), and the Sheikh also collected the news of the Imam (peace be upon him) in a book he called (Uyun Akhbar al-Ridha), and Sheikh Dawud bin Suleiman al-Ghazi compiled his hadiths (peace be upon him) in a book He named it (Musnad Al-Ridha), and the same thing was done by Professor Aziz Allah Mercury by collecting his hadiths (peace be upon him) in a book called (Musnad Al-Ridha) (peace be upon him). And there are aspects that the researchers did not study, research, audit, and so on Here is his interpretation of a large number of verses of the Noble Qur’an that scholars (peace be upon him) transmitted from him in their books, especially the great scholar and the great Sheikh (al-Saduq) (may God rest his soul) in his book (Al-Amali), where we found a fair number of verses that the Imam (peace be upon him) interpreted During his debates as a protest from him (peace be upon him) against the opponent, or a statement from him to ask a person about the meaning of a specific verse, we found it deserving of research and attention. By extracting his (peace be upon him) interpretation of these verses and looking into what the commentators of Islam said about them, and trying to retrace the correct and consistent interpretation of reason, transmission and logic by collecting what we can from the rational and translational evidence and clues indicating that the interpretation of the Imam (peace be upon him) is the correct and consistent interpretation of the Holy Qur’an and the Sunnah of the Prophet. Especially when he is one of the imams of the People of the House (peace be upon them), the people of remembrance and the Qur’an who the Almighty said about them: In houses that God has permitted to be raised and mentioned in them His name shall be praised for Him in the foreground. And two studies and a conclusion, in the preface: We showed two important aspects that must be necessary before entering into the midst of the research, the first aspect: explaining the meaning of (interpretation) in the language and the Sharia - the convention - and the second aspect: we provided a brief translation of the life of our Imam Al-Reza (peace be upon him), and we also knew With our Sheikh (Al-Saduq) and his book (Al-Amali), and in the two studies, we dealt with his (peace be upon him) interpretation of the Qur’anic verses and arranged them in the search according to their order in the Qur’an. The first topic was: Interpretation of the Meccan verses, and as we said it was (nine verses), and they are: 1- A verse from Surat al-An’am 2- verse from Surat Al-Hijr, 3- verse from Surat Al-Israa, 4 and 5- two verses from Surat Taha, 6- verse from Surat Al-Shura, 7 and 8- two verses from Surat Al-Anbiya, 9- verse from Surat Yassin, and the second topic: Interpretation of the verses Al-Madaniya (five verses) and they are: 1- a verse from Surat al-Baqara, 2- a verse from Surat Al-Imran, 3- a verse from Surat al-Nisa, 4- a verse from Surat al-Anfal, 5- verse from Surat al-Raad, and then the conclusion was, after it List of sources and references.